GURU PROFESIONAL DALAM PERSPEKTIF AL-QUR'AN DAN HADIST - Hayatul khairi; Yelfi Dewi; Dela Desra Murni; Amirul Akbar Marfit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to analyze teacher professionalism from the perspective of the Qur'an and Hadith. In the context of Islamic education, teacher professionalism is defined as the abilities and attitudes that must be possessed by educators to educate students effectively. The Qur'an emphasizes the importance of characteristics such as patience, gentleness, justice, and mastery of teaching materials. Meanwhile, the Hadith of the Prophet Muhammad SAW emphasizes sincere intentions, caring attitudes towards students, and the ability to communicate effectively. This study uses a literature study approach by reviewing various sources of the Qur'an and Hadith as well as Islamic education literature. The results of the study of teacher professionalism according to the perspective of the Qur'an are not only limited to mastery of teaching materials, but also include moral and ethical aspects. By understanding the values ​​contained in the Qur'an, it is hoped that educators can improve the quality of education and produce a generation that is not only academically intelligent but also has good morals. Teacher professionalism according to the Hadith includes various aspects, from the right intentions to fair and caring attitudes towards students. By understanding these values, it is hoped that educators can improve the quality of their teaching and contribute to the achievement of better educational goals.